2020
DOI: 10.1007/s41701-020-00078-w
|View full text |Cite
|
Sign up to set email alerts
|

Question Tags in Philippine English

Abstract: This study investigates the use of question tags (QTs) in a subcorpus of dialogues from the Philippine component of the International Corpus of English. It takes into account the full range of QT forms used in Philippine English, including English variant QTs as well as English and Tagalog invariant forms. The analysis investigates the effects of text type and pragmatic function on the selection of particular forms. The results show that Filipino speakers use English and Tagalog forms to almost equal proportio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(12 citation statements)
references
References 27 publications
(38 reference statements)
2
10
0
Order By: Relevance
“…The strong dominance of invariant forms in general and the use of many indigenous forms is in line with other studies on New Englishes that have also investigated variant and invariant question tags (Wilson et al, 2017;Mbakop, 2020;Westphal, 2020). In contrast (Gómez González, 2018: 122) shows a higher frequency of variant than invariant question tag forms for British English.…”
Section: Discussion and Conclusion: The Multilingual Pragmatics Of Ni...supporting
confidence: 85%
See 4 more Smart Citations
“…The strong dominance of invariant forms in general and the use of many indigenous forms is in line with other studies on New Englishes that have also investigated variant and invariant question tags (Wilson et al, 2017;Mbakop, 2020;Westphal, 2020). In contrast (Gómez González, 2018: 122) shows a higher frequency of variant than invariant question tag forms for British English.…”
Section: Discussion and Conclusion: The Multilingual Pragmatics Of Ni...supporting
confidence: 85%
“…The corpus-pragmatic analysis of six dialogue text types of ICE-Nigeria has shown that Nigerian speakers use a wide range of English and non-English question tag forms. Similar multilingual variation has been described for Cameroonian (Mbakop, 2020), Philippine (Westphal, 2020), and Trinidadian English (Wilson et al, 2017). In contrast to the overwhelming focus on variant question tags in previous research (e.g., Tottie and Hoffmann, 2006;Borlongan, 2008;Barron, 2015;Parviainen, 2016;Hoffmann et al, 2017) in World Englishes, these types of question tags are marginal in Nigerian English as they only account for 2.5% of occurrences.…”
Section: Discussion and Conclusion: The Multilingual Pragmatics Of Ni...supporting
confidence: 49%
See 3 more Smart Citations